Consultations populaires québécoises et référendums fédéraux - Brun, Henri; Tremblay, Guy (Les Cahiers de droit, 1979)
This article expresses criticism about, and makes comparisons between, Quebec's new legislation on referenda and the federal bill (not yet adopted) on the same subject. The authors' claim is that the most commonly heard comments about these legislative pieces seem to miss the most important target. The limitations and controls of referendum expenses, prescribed by the Quebec Act and loudly denounced by the opposition, on the whole seem preferable to the lightly hidden laxity of the federal bill. On the other hand, in both cases the general inadequacy of the means of control makes the referendum process a very powerful weapon in the hands of governments. These new pieces of legislation give much to the governments, little to the people.